Force-velocity relationship of muscles performing multi-joint maximum performance tasks - Jaric, S. (International Journal of Sports Medicine, 2015)
Manipulation of external loads typically provides a range of force, velocity, and power data that allows for modeling muscle mechanical characteristics. While a typical force-velocity relationship obtained from either in vitro muscles or isolated muscle groups can be described by a hyperbolic equation, the present review paper reveals the evidence that the same relationship obtained from maximum-performance multi-joint movements could be approximately linear. As a consequence, this pattern also results in a relatively simple shape of the power-velocity relationship. The parameters of the linear force-velocity relationship reveal the maximum force, velocity and power. Recent studies conducted on various functional movement tasks reveal that these parameters could be reliable, on average moderately valid, and typically sensitive enough to detect differences among populations of different physical abilities. Therefore, the linear force-velocity relationship together with the associated parabolic power-velocity relationship could provide both a new and simplified approach to studies of the design and function of human muscular system and its modeling. Regarding the practical applications, the reviewed findings also suggest that the loaded multi-joint movements could be developed into relatively simple routine tests of the force-, velocity- and power-generating capacity of the neuromuscular system.